Effects of a modified muscle sparing posterior technique in hip hemiarthroplasty for displaced intracapsular fractures on postoperative function compared to a standard lateral approach (HemiSPAIRE): protocol for a randomised controlled trial. Issue 6 (8th June 2021) - Price, Anna; Ball, Susan; Rhodes, Shelley; Wickins, Robert; Gordon, Elizabeth; Aylward, Alex; Cockcroft, Emma; Morgan-Trimmer, Sarah; Powell, Roy; Timperley, John; Charity, John
Abstract : Introduction: Currently National Institute for Health and Care Excellence clinical guidelines in the UK suggest that surgeons performing partial hip replacements (hemiarthroplasty) should consider using the lateral approach. Alternatively, a newer, modified posterior approach using a muscle sparing technique named 'Save Piriformis and Internus, Repairing Externus' (SPAIRE) can be used leaving the major muscles intact. This randomised controlled trial (RCT) aims to compare the SPAIRE approach to the standard lateral approach, to determine if it allows patients to mobilise better and experience improved function after surgery. Methods and analysis: HemiSPAIRE is a two-arm, assessor-blinded, definitive pragmatic RCT with nested pilot and qualitative studies. Two hundred and twenty-eight participants with displaced intracapsular fractures requiring hip hemiarthroplasty will be individually randomised 1:1 to either the SPAIRE, or control (standard lateral approach) surgical procedure. Outcomes will be assessed at postoperative day 3 (POD3) and 120 (POD120). The primary outcome measure will be level of function and mobility using the Oxford Hip Score at POD120. Secondary outcomes include: De Morton Mobility Index (DEMMI), Cumulated Ambulatory Score and Numeric Pain Rating Scale (NPRS) at POD3; DEMMI, NPRS and EQ-5D-5L at POD120, complications, acute and total length of hospital stay, and mortality. Primary analysis will be on an intention-to-treat basis. Participant experiences of the impact of surgery and recovery period will be examined via up to 20 semi-structured telephone interviews. Ethics and dissemination: The protocol has been approved by Yorkshire and the Humber—Bradford Leeds Research Ethics Committee. Recruitment commenced in November 2019. Findings will be disseminated via research articles in peer-reviewed journals, presentations at conferences, public involvement events, patient groups and media releases. A summary of the trial findings will be shared with participants at the end of the study. Trial registration number: NCT04095611 .